Volunteers in public schools - Michael, Bernard (National Academy Press, 1990)
Offers an overview of volunteer activity in US public schools - reporting on how volunteers are being used in schools, what factors make programs successful, what research will enhance our ability to create good programs, and what directions our national policy should take.
Keywords: Volunteer workers in education -- United States.; Volunteer workers in education -- United States -- Statistics.; Volunteer workers in education.; Bénévoles en éducation.; Bénévoles en éducation -- États-Unis.; Bénévoles en éducation -- États-Unis -- Statistiques.; EDUCATION -- Administration -- General.; Volunteer workers in education; United States; Schule; Volontär; USA; Statistics